2022
DOI: 10.1080/02607476.2022.2082272
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing professional empathy to mitigate for marginalisation and the critical gaze in teacher development: a phenomenological framework

Abstract: Empathy is a form of perception in which individuals access the perspectives of others about the world in order to build knowledge about it. It is also a source of self-knowledge because, as a consequence of learning how others see us, we can regulate and refine how we see ourselves. Empathy is, therefore, an important capacity through which social cohesion is created. The aim of this paper is to consider the role of professional empathy between teachers when they engage in collective professional development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Researchers reveal the crucial need for educators to strengthen their skills as much as their qualifications, to effectively deliver the curriculum (Carlson, et al, 2019;Neumann, et al, 2019). Research studies have recommended that educators should increase their curriculum knowledge, pedagogical content understanding, and teaching abilities (Sulaimani, et al, 2017;Van Driel & Berry, 2012;Bayar, 2014;Gore & Rosser, 2022;Campbell, 2022). Focusing on curricular content and how to effectively deliver it has continually been highlighted as fundamental to the success of professional development (Geldenhuys & Oosthuizen, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers reveal the crucial need for educators to strengthen their skills as much as their qualifications, to effectively deliver the curriculum (Carlson, et al, 2019;Neumann, et al, 2019). Research studies have recommended that educators should increase their curriculum knowledge, pedagogical content understanding, and teaching abilities (Sulaimani, et al, 2017;Van Driel & Berry, 2012;Bayar, 2014;Gore & Rosser, 2022;Campbell, 2022). Focusing on curricular content and how to effectively deliver it has continually been highlighted as fundamental to the success of professional development (Geldenhuys & Oosthuizen, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Focusing on curricular content and how to effectively deliver it has continually been highlighted as fundamental to the success of professional development (Geldenhuys & Oosthuizen, 2015). Recent studies have emphasized that professional development activities should be offered according to the existing needs of educators and learners (Campbell, 2022;Matherson & Windle, 2017). Extant studies have indicated that successful professional development programmes must consider both subject knowledge and subject-specific teaching techniques (Van Driel & Berry, 2012;.…”
Section: Literature Reviewmentioning
confidence: 99%